2014
DOI: 10.4236/jdm.2014.44040
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Prevalence of Diabetes and Prediabetes in Patients of Non-Alcoholic Fatty Liver Disease and the Impact of Diabetes on Liver Histology in Coastal Eastern India

Abstract: Background and Objectives: Non-alcoholic fatty liver disease (NAFLD) is more common in diabetic patients. There are limited studies on clinical, biochemical and histological features of NAFLD patients who are diabetic. The aim of the study was to determine the prevalence of diabetes and prediabetes in a cohort of NAFLD patients and to compare anthropometry, biochemical and metabolic parameters and hepatic histology of diabetic NAFLD patients with non-diabetic NAFLD patients. Methods: 515 consecutive NAFLD pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
4
10
0
Order By: Relevance
“…Majority of the patients (45%) were overweight, 42.5% had Grade I obesity, while only 12.5% were normal weight subjects in the study. The outcome well-matched with the studies of Duseja A and Singh SP et al where in the highest prevalence is seen among patients with BMI > 25 10,19 . This study is consistent with Amarapurkar D et al, Alam S et al, Singh SP et al, Somalwar AM et al and Hu X et al 13,14,23,24,25 Effect on Subjective Parameters Anorexia: In this study assessing anorexia before and after the treatment at various assessment days, it was found that, 7(35%) patients had mild anorexia, 1(5%) patient had moderate anorexia, 12 (60%) patients had no anorexia at baseline in group-A while 9 (45%) patients had mild anorexia, 1 (5%) patient had moderate anorexia, and 10 (50%) patients had no anorexia at baseline in group-B.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Majority of the patients (45%) were overweight, 42.5% had Grade I obesity, while only 12.5% were normal weight subjects in the study. The outcome well-matched with the studies of Duseja A and Singh SP et al where in the highest prevalence is seen among patients with BMI > 25 10,19 . This study is consistent with Amarapurkar D et al, Alam S et al, Singh SP et al, Somalwar AM et al and Hu X et al 13,14,23,24,25 Effect on Subjective Parameters Anorexia: In this study assessing anorexia before and after the treatment at various assessment days, it was found that, 7(35%) patients had mild anorexia, 1(5%) patient had moderate anorexia, 12 (60%) patients had no anorexia at baseline in group-A while 9 (45%) patients had mild anorexia, 1 (5%) patient had moderate anorexia, and 10 (50%) patients had no anorexia at baseline in group-B.…”
Section: Resultssupporting
confidence: 88%
“…The baseline demographic data has been given in Table no [10][11][12][13][14] A majority of trial subjects (52.5%) registered were males and 47.5% were females, which supports the results stated by Singh et al and Ajay Duseja that non-alcoholic fatty liver is more common in males than females 1,15 . The gender differences in NAFLD and NASH can be probably explained by gender disparities in body fat distribution, lifestyle, and sex hormone metabolism 16 .…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Currently, non-alcoholic fatty liver disease (NAFLD) is considered to be an integral part of the metabolic syndrome with insulin resistance as a central pathogenic factor. It is considered nowadays that NAFLD may represent a risk factor for development of adenomatous polyps, however little is known about the possible association between colorectal neoplasms and NAFLD [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…A study from coastal eastern India has shown that both in NAFLD patients, insulin resistance was closely associated not only with fatty liver but also histologically severe disease [28]. Thus, NAFLD might represent another feature of the metabolic syndrome, with decreased insulin sensitivity being the common factor [29].…”
Section: Odds Ratio (P Valuementioning
confidence: 99%